The Relationship Between The Frequency Of Chemotherapy With The Functional Status Of Cancer Patients Who Undergone Chemotherapy In RSUP Sanglah Denpasar - Kadek Ari Melia Endrawati (Program Studi Sarjana Ilmu Keperawatan dan Profesi Ners, Fakultas Kedokteran, Universitas Udayana, 2013)
Cancer is a condition in which cells have lost their control and normal mechanism, is one of treatment for cancer therapy is chemotherapy. The frequency of chemotherapy in cancer patients is the number of patients doing treatment with cytostatic medicines. The functional status of cancer patients is an ability to perform daily activities included at work, self-care and maintenance of family or social roles that can be affect by the patient condition and the therapy. The aim of this research was to analyze the relationship between the frequency of chemotherapy with the functional status of cancer patients who undergone chemotherapy in RSUP Sanglah Denpasar. This research include in descriptive correlational and used cross-sectional method approach. Samples were taken from 38 patient with nonprobability sample selection technique with the purposive sampling. The analysis technique of the data to examine the hypothesis is correlation product moment (p<0.05). The result of this research showed the average score of the chemotherapy frequency is four times with the minimal frequency is two times and the maximal is eight times, the average score of functional status is 24,03. The p-value is 0.000 which means p<0.05 so the H0 is rejected and the r-value is (-0,745) with an absolute value is 0,745, then it can be stated there was a strong correlation and inversely between the frequency of chemotherapy with the functional status of cancer patients who undergone chemotherapy. Based on this result, it can be suggest nurses should increase their roles in providing care for cancer patients who undergone chemotherapy, to maintain their functional status during chemotherapy.